DAS181 Treatment of Severe Parainfluenza Virus 3 Pneumonia in Allogeneic Hematopoietic Stem Cell Transplant Recipients Requiring Mechanical Ventilation - B. Dhakal; A. D’Souza; M. Pasquini; W. Saber; T. S. Fenske; R. B. Moss; W. R. Drobyski; P. Hari; M. Z. Abidi (Case Reports in Medicine)
Parainfluenza virus (PIV) may cause life-threatening pneumonia in allogeneic hematopoietic stem cell transplant (HSCT) recipients. Currently, there are no proven effective therapies. We report the use of inhaled DAS181, a novel sialidase fusion protein, for treatment of PIV type 3 pneumonia in two allogeneic hematopoietic SCT recipients with respiratory failure.